A Comparative Study of Object-Oriented Programming Vs Procedural Programming - Shreasth, Rajni (International journal for research in applied science and engineering technology, 2025)
This research paper offers a detailed comparative exploration of Object-Oriented Programming (OOP) and Procedural Programming (PP), two foundational paradigms that have significantly influenced the evolution of software development. It delves into their underlying principles, tracing the conceptual and structural distinctions that define each approach. The discussion highlights the historical development of both paradigms, examining how they emerged and gained prominence in different eras of computing. Rather than relying on empirical data or case studies, this study employs a theoretical and literature-based methodology to analyze core aspects such as modularity, code reusability, abstraction, and ease of maintenance. The paper outlines the strengths and limitations inherent in each paradigm, offering insights into how their respective features align with particular types of software development tasks. Object-Oriented Programming is emphasized for its encapsulation, inheritance, and polymorphism, which support scalable and maintainable code, particularly in complex systems. In contrast, Procedural Programming is examined for its simplicity, linear logic, and suitability for tasks requiring straightforward algorithmic implementation. The research also considers the implications of both paradigms in educational contexts, discussing how learners engage with each model and how they influence programming comprehension and design thinking. By synthesizing insights from programming language theory and academic literature, this study seeks to clarify the circumstances under which each paradigm is most effective. It ultimately provides readers with a structured framework for evaluating the suitability of OOP or PP depending on the goals, scale, and nature of a software project. The absence of casespecific or survey-based data ensures that the focus remains on conceptual depth and theoretical clarity, making this paper a valuable resource for learners, educators, and developers seeking a foundational understanding of programming paradigms.